Evaluasi Kurikulum Pendidikan Agama Islam di Madrasah dalam Meningakatkan Karakter Peserta Didik - Durrotun Baidok; Saiful Arif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
One of the primary goals of national education is character development, which must be achieved through the learning process in madrasahs. In this context, Islamic Religious Education (IRE) plays a crucial role in instilling moral, spiritual, and social values in students. However, the success of character development depends not only on the availability of IRE teaching materials but also on the quality of the curriculum and the effectiveness of its implementation. This article aims to evaluate the role of the Islamic Religious Education curriculum in madrasahs in enhancing student character through a literature review. The research method used is a literature review, which involves the collection and analysis of various scientific sources, including books, journal articles, and documents related to the IRE curriculum and character education. The study results indicate that the IRE curriculum integrates various character values—such as religiosity, honesty, discipline, responsibility, tolerance, and social concern—into its objectives, content, and learning activities. The implementation of the curriculum, supported by exemplary teacher behavior, madrasah culture, and religious habit-forming programs, contributes positively to students’ character development. Nevertheless, several challenges remain, including the lack of a comprehensive character evaluation system. character assessment, differences in students’ backgrounds, and the lack of optimal collaboration among schools, families, and communities. Therefore, continuous curriculum evaluation is necessary to ensure that the objectives of character education can be achieved effectively and sustainably within the madrasah environment.